New Aspects of Neurotransmitter Releasee and Exocytosis: Regulation of Neurotransmitter Release by Phosphorylation - Masami Takahashi; Makoto Itakura; Masakazu Kataoka (Elsevier, 2003)
ABSTRACT: Synaptic transmission is conducted by neurotransmitters released from nerve terminals. Neurotransmitter release is regulated both positively and negatively by multiple mechanisms, and its regulation is believed to be one of the important mechanisms of synaptic plasticity underlying learning and memory. Various protein kinases play important roles in the regulation, and candidates for protein substrates essential for the regulation have been identified.